ANTIBACTERIAL ACTIVITY OF TAMARIX APHYLLA L. LEAVES EXTRACT ON HETEROGENEOUS VANCOMYCIN ITERMEDIATED STAPHYLOCOCCUS AUREUS (hVISA) - Osamah Z. Al-Hayali; M. F. AL Marjani; A. Maleki (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to examine the antibacterial activity of the T. aphylla leaves ethanolic extract in vitro against the locally strain heterogeneous vancomycin intermediated Staphylococcus aureus (hVISA) at different concentrations starting from 0.03 to 200 mg/ml. T.aphylla leaves were extracted by ethanol 96% in the Soxhlet extraction unit. Using both gas chromatography and mass spectrometry (GC/MS), the results indicated that the composition of T. aphylla extract was oil and include a variety of chemicals, including 9,12-Octadecadienoic acid, methyl ester (20.06%), followed by Phytol, acetate (18.93%) and Hexadecanoic acid, methyl ester (12.14%), were in leaves. The concentration of 1.5 (mg/ml.) was determined as a minimum inhibitory concentration (MIC) for hVISA antibacterial activity. Gene expression was detected using the Quantitative Real-Time PCR technique; before and after treatment with T. aphylla leaves extracts; the gene expression was low after treatment with T. aphylla leaves extracts. In conclusion, T. aphylla leaves extract is a promising alternative medication that can treat the infection caused by hVISA.